FAKTOR BEKERJA DAN FAKTOR PENGETAHUAN IBU DENGAN KEHADIRAN BALITA DATANG DITIMBANG KE POSYANDU - Ni Nyoman Sri Adnyani; I Made Purnadhibrata; A A Agung Ngurah Kusumajaya (Jurnal Ilmu Gizi : Journal of Nutrition Science, 2022)
The issue of nutrition is one of the important factors, even a determinant of the success of Indonesia's human development efforts. Posyandu is one of the health services in the village to facilitate the community to find out or check their health, especially for pregnant women and children under five. The purpose of the study was to determine the relationship of maternal participation with knowledge and employment status. The type of research used is descriptive, a method that serves to analyze or describe a research result. The subjects used in the literature review were 2 theses that involved the factors of maternal participation in posyandu. These activities include searching, reading, and sorting out research studies and library materials that contain theories relevant to the research to be conducted. Literature analysis is done by summarizing the results of research in journals and theses that are relevant to the issues discussed. The results of this study indicate that the factors causing the absence of children under five come and are weighed to the posyandu because of low knowledge of 52.2% - 57.0%. And the cause of absence due to working factors was 62.7%.keywords: maternal participation, knowledge, employment status.